Effectiveness and safety of NER1006 versus standard bowel preparations: A meta-analysis of randomized phase-3 clinical trials. Issue 8 (August 2020) - Maida, M.; Macaluso, F.S.; Sferrazza, S.; Ventimiglia, M.; Sinagra, E.
Abstract: Background: A 1 L PEG-based preparation for colonoscopy (NER1006) has been recently developed. Aims: We conducted a meta-analysis of randomized controlled trials (RCTs) to explore the effectiveness and safety of NER1006 versus traditional preparations. Methods: PubMed/Medline and Embase were systematically searched through January 2020 for phase-3 RCTs comparing NER1006 versus standard preparations. Results: Three RCTs (1879 participants) met the inclusion criteria and were included. The analysis showed a higher cleansing success for NER1006 compared standard preparations (OR=1.28; 95% CI 1.00–1.62; p = 0.047, I 2 =0%) as well as a greater high-quality cleansing of the right colon (OR=2.13; 95% CI 1.16–3.94; p = 0.015, I 2 =76.0%) when assessed by the Harefield Cleansing Scale (HCS). The pooled estimate of the NER1006 effect on ADR showed a higher, although not significant, ADR of the right colon (OR=1.19; 95% CI 0.73–1.92; p = 0.485, I 2 =53%). When considering the impact of NER1006 on mild to moderate treatment-emergent adverse events (TEAEs), we observed a significant pooled estimate of TEAEs (OR=2.31; 95% CI 1.82–2.94; p <0.001, I 2 =0%). Conclusions: When compared to traditional preparations, NER1006 showed a better overall cleansing of the colon as well as a greater high-quality cleansing of the right colon, with comparable ADR. A higher incidence of mild to moderate TEAEs was observed for NER1006, in the absence of serious adverse events.